The Employee Performance in the Covid-19 Pandemic and Its Antecedents - Eddy Madiono Sutanto; Lady Valentine (Master of Management, School of Business and Management, Petra Christian University, 2022)
Indonesia is currently experiencing a Covid-19 pandemic. The Covid-19 pandemic has had a bad impact on the majority of Indonesians. Companies in Indonesia were severely affected. Many companies have experienced a decrease in turnover and sales. This situation has resulted in a reduction in employees to a cut in wages. Company policy is undoubtedly not allowed to decrease employee performance, therefore. This study aimed to determine the effect of perceptions of salary on employee performance through work motivation. The research subject was the employees in Surabaya who experienced salary cuts due to the Covid-19 impact. The sampling technique was purposive sampling. The total number of respondents was 88. The PLS results showed that employees' perceptions of salary did not affect employee performance. Perceptions of salary only affected work motivation. Work motivation affected employee performance, but work motivation did not mediate the effect of perceptions of salary on employee performance.